Influence of different levels of aluminum on the development of citrus rootstock Swingle Citrumelo (Citrus paradisi mcf. x Poncirus trifoliata raf.) in nutrient solution - Santos, C. H. dos; Grassi, H.; Rodrigues, J. D.; Pinho, S. Z. de (Inst Tecnologia Parana, 2000)
This work aimed at evaluating the influence of different levels of aluminum on the physiological parameters of the citrus rootstock Swingle Citrumelo in hydroponic solution. The experiment was carried out with a completely randomized design with three replications, subdivided in several lots. The levels of aluminum used were: 0, 7.5, 15 22.5 and 30 mg L-1 inform of AlCl3. 6H(2)O in nutrient solution. Following physiological parameters were evaluated: specific and relative foliar area, relative foliar mass, and the ratio of aerial part dry matter/root system dry matter. The results shelved that aluminum did not influence the parameters evaluated except the specific foliar area, which decreased starting at the 7.5 mg L-1 level.
Keywords: citrus; rootstocks; aluminum; mineral nutrition; growth analysis